CCR9 shapes the immune microenvironment of colorectal cancer modulating the balance between intratumoral CD8+ T cell and FoxP3+ Helios+ Treg subpopulations - Jacobo Martínez-Ríos; Cynthia Paola López-Pacheco; Eduardo Alberto García-Zepeda; Gloria Soldevila (PLoS ONE, 2025)
Colorectal cancer (CRC) is the third most common cancer in the world and the second cause of death related to cancer. Regulatory T cell (Treg) infiltration is enriched in several tumor types including CRC and correlates with suppression of the anti-tumor immune response. In the large intestine, thymic Tregs (tTregs Helios+) and peripheral Tregs (pTregs Helios−) coexist and maintain intestinal homeostasis under steady state conditions. The recruitment of Treg cells to the intestine is orchestrated by the CCR9/CCL25 axis, which is potentiated under inflammatory conditions. Interestingly, the balance between cytotoxic CD8+ T cells and Tregs within the tumor microenvironment is critical for antitumor immunity and cancer progression. An elevated CD8+/Treg ratio has been associated with improved clinical outcomes in various cancers, including CRC. Therefore, here we investigate the potential role of chemokine receptor CCR9 on CD8+/Treg ratio and the effect of the recruitment of Treg subpopulations (Helios+ and Helios−) into the tumor microenvironment using the AOM/DSS induced colitis-associated colorectal cancer murine model. Our findings reveal that CCR9 deficiency leads to distinct alterations in the CRC microenvironment, characterized by decreased intratumoral Tregs Helios+. Also, the lack of the receptor leads to an improvement of the antitumor immune response, increasing the CD8+/Treg ratio within the tumor immune infiltrate. These results underscore the importance of CCR9 in shaping the immune microenvironment during CRC development.